Sinonasal Teratocarcinosarcoma - S, Shaikh; Fernandes, G; Rojekar, A; Joshi, A (International Journal of Medical Research and Review, 2016)
Sinonasal Teratocarcinosarcoma (SNTCS) is an extremely rare and unusual malignant neoplasm of the sinonasal tract with an aggressive behaviour. Till date, there are less than a hundred cases reported in literature. A 52 year old patient presented with a large, reddish brown, right sided nasal mass with epistaxis since 1 month. Histopathology revealed a highly malignant tumor with diverse histomorphological features and was labelled SNTCS. These unique tumors show diverse histomorphological features of a carcinosarcoma with teratoid elements. Immunohistochemistry was positive for cytokeratin, vimentin, GFAP, NSE, S-100. Chemotherapy with cisplatin and etoposide was given followed by a debulking surgery. The patient is well seven months after diagnosis and scheduled for radiotherapy. Diagnosis of SNTCS requires an adequate representative biopsy and extensive sampling on Histopathology. Treatment required included surgery, chemotherapy and radiotherapy.